Formula Study on High Temperature Corrosion Inhibitor for CO2/O2 in Oil Recovery during Fire Flood. Issue 1 (September 2020) - Yan, Xuanqi; Jiang, Weiqi; Wang, Yingrui; Zhang, Lili; Su, Na; Shang, Fang; Du, Qingzhen; Yao, Shangsheng; Chen, Xi; Liu, Zhigang
Abstract: The purpose of this paper is to develop a kind of high temperature corrosion inhibitor and to resolve the problem of CO2/O2 corrosion in high temperature oil well. The experimental methods include CO2/O2 corrosion simulation experiment, screening experiment, formula compounding and orthogonal experiment which are used to test the corrosion inhibition rate at different temperature and concentration. HZ-9 high temperature corrosion inhibitor for CO2/O2 is developed in high temperature oil well during fire flood. The main component of HZ-9 is imidazoline quaternary ammonium salt, sodium isoascorbate assisting with high temperature resistant fluorocarbon imidazoline which has good corrosion inhibition effect with the corrosion inhibition rate is above 80%. The conclusion is HZ-9 can resolve CO2/O2 corrosion in high temperature oil well during fire flood.